Knowledge and practices of community pharmacists towards non-prescription dispensing of antibiotics in Northern Nigeria - Abubakar, Usman; Tangiisuran, Balamurugan (Springer, 2020)
Abstract Background Non-prescription dispensing of antibiotics is common in Nigeria and this could contribute to the emergence of microbial resistance. Objectives To evaluate knowledge, perception and practices of community pharmacists towards dispensing antibiotics without prescription. Setting Community pharmacies in two cities in Northern Nigeria. Methods A prospective cross-sectional study was conducted among community pharmacists in two cities in Northern Nigeria, using a validated and pilot-tested questionnaire. The questionnaire was self-administered and data was collected between 06th April and 31st May 2019. The data was analyzed using descriptive and inferential analyses. Main outcome measure Knowledge, perception and practices towards dispensing antibiotics without prescription. Results A total of 98 out of 130 community pharmacists completed and returned the questionnaire (response rate: 75.3%). About two-third (64.3%) of the community pharmacists were aware that dispensing antibiotics without prescription is illegal. However, this malpractice was common as 39.7% of the respondents indicated that they dispensed antibiotics without prescription five times or more in a day. Antibiotics dispensed without prescription were used for the treatment of urinary tract infections (83.7%), typhoid fever (83.7%) and sexually transmitted infections (66.3%). Pharmacist’s confdence in knowledge of antibiotic therapy was the most common reason for non-prescription dispensing of antibiotics. Respondents with less than 5 years of working experience (66.7%) were signifcantly more likely to dispense antibiotics without prescription 5 times or more in a day compared to those with more than 5 years community pharmacy experience (33.3%), P = 0.031. Conclusion Non-prescription dispensing of antibiotics was common among community pharmacists despite awareness about its prohibition and implications. The malpractice was associated with number of years of community pharmacy experience. Confdence in knowledge of antibiotic therapy was the main reason community pharmacists dispensed antibiotics without prescription. Continuous pharmacy education and training on handling of antibiotics may help to reduce inappropriate practices among community pharmacists.